Enhance Marketing Fresh Fruit in Sambu Market Medan North Sumatera - Lasrotua Effendi Hasibuan; Miftah El Fikri; Hernawaty (Budapest International Research and Critics University, 2022)
The fresh fruit business at the certain Shop at the Sambu market has the field been around for a long time, namely since 1997 with a workforce of 3 people from their family members. The fresh fruit business has a fairly high market opportunity among the businesses in Medan's Sambu market, due to a large number of buyers and a large number of enthusiasts, but the Covid 19 has had a major impact on the declining sales lately, plus other shops. other fruit shops, know the advantages of marketing fresh fruit. Collecting data using interview instruments and questionnaires using the variables of imaging, product quality, price, and customer loyalty. The data analysis method is a combination of qualitative and quantitative methods which is an approach in research that combines and connects quantitative and qualitative research methods. This study used 60 samples taken from respondents. adjusted R Square number of 0.973 which can be called the coefficient of determination which in this case means that 97.3% of customer loyalty can be obtained, Product Quality and Price. While the remaining 100% - 97.3% = 2.7% is explained by other factors or variables outside the model. Such as Place, Service, promotion, etc.